Transformacja kosmosu w literaturze międzytestamentalnej - Parchem, Marek (Verbum Vitae, 2017)
In the intertestamental literature, especially from various writings of an apocalyptic nature, a recurring motif emerges of the transformation of the universe as the final phase of eschatological events. In the last days, the world – being infected with sin and dominated by the powers of evil – will be renewed and transformed by God into a perfect reality wherein justice and goodness will prevail. In the present article, this notion of the transformation of the universe is explored and discussed. The idea appears in various documents of the intertestamental literature, namely, certain exegetical works such as The Book of Jubilees (Jub 1:29; 4:26) and Biblical Antiquities of Pseudo-Philo (LAB 3:10); the Qumran Rule of the Community (1QS 4:25); and several apocalypses: The Book of Heavenly Luminaries (1 Enoch 72:1), The Apocalypse of Weeks (1 Enoch 91:14-17), The Animal Apocalypse (1 Enoch 90:37-38), The Book of the Similitudes (1 Enoch 45:4-5), The Fourth Book of Ezra (4 Ezra 7:28-31, 75, 113-114), and The Syriac Apocalypse of Baruch (2 Bar 32:1-6; 57:1-3).